Pollution loads and inert COD in the laying chicken industry - (:unkn) unknown (IWA Publishing, 1999)
Modern laying chicken plants generate strong wastewaters of limited flow rate, with COD concentrations up around to 10 g l −1 , with a soluble portion of 50% and high nitrogen and phosphorus contents. The unit wastewater flow is as low as 0.003-0.005 1 chicken −1 day −1 and the unit organic load is assessed as 0.03 g COD chicken −1 day −1 . COD fractionation reveals that the soluble residual portion accounts for 350 mg l −1 in the chicks step and 980 mg l −1 in the laying step for aerobic treatment. When anaerobic treatment is applied this residual fraction is likely to exhibit an increase of around 60 to 80 %. These observations underline the significance and the need of setting effluent limitations attainable by biological treatment, if evidence is presented that they do not pose appreciable environmental problems such as toxicity, colour, etc. This is especially true for laying chicken plant effluents, due to their intermittent mode of generation and their limited volume.